CODE CHOICE USED IN YOUTUBE CONTENT “NEBENG BOY” - Caecilia Ivana Angelia (Prasasti: Journal of Linguistics)
Nebeng Boy is one of the most popular YouTube content created by Indonesian YouTuber and an ex-Video Jockey from MTV, Boy William. The participants in this YouTube content are divided into two; the Host and the Guests. This research aims to find out the code choices chosen by the participants of YouTube content “Nebeng Boy” and the reasons why the participants choose the different codes.